Unlocking Electrochemical-Driven Surface Oxygen Vacancies-Regulated Cathode–Electrolyte Interphase for Stabilizing Li-Ion Cells - Yan, Chenxi; Liu, Xing; He, Xuanlong; Han, Junjie; He, Longjun; Tian, Na; Wang, Yanyi; Li, Qiang; Zhao, Ning; Zhang, Lipeng; Zhang, Peixin; Ma, Dingtao (Nano-Micro Letters, 2026)
A stable cathode–electrolyte interphase (CEI) significantly enhances the durability of lithium-ion batteries; however, the intricate chemistry underlying its formation makes predesign exceedingly challenging. This work demonstrates that surface oxygen vacancy (OV) concentration dually regulates CEI thickness and composition. We develop an in situ strategy where Li2C4O4 incorporation into LiCoO2 (LCO) spontaneously decomposes during cycling, generating surface OVs. Combined experimental and theoretical calculations reveal these OVs enhance interfacial electron/Li⁺ migration rates while stabilizing the CEI. Notably, through 18O isotope labeling with time-of-flight secondary ion mass spectrometry, we innovatively provide direct experimental evidence that surface lattice oxygen serves as the predominant oxygen source for CEI oxygen-containing decomposition products, establishing the mechanism for OV-mediated CEI modulation. Based on this theory, the linear correlation and causal relationship among Li2C2O4 content, surface OV concentration, and LiF/LixPOyFz ratio in CEI are revealed. This strategy endows the OV-rich LCO cathode with 71.1% capacity retention after 600 cycles at 1 C within 3–4.4 V (23.9% for bare LCO) and achieves universal validation at 4.5 V and in LiNi0.8Co0.1Mn0.1O2 (NCM811). This study elucidates the critical function of surface OVs in prolonging cycle life and establishes a new design principle for tailored cathode interfaces and CEI chemistry. Highlights: 1 In situ electrochemically induced surface oxygen vacancies (OVs) by Li2C4O4 decomposition enable dual regulation of cathode electrolyte interphase (CEI) thickness and composition, a novel strategy for tailored CEI engineering in Li ion batteries. 2 For the first time,18O isotope labeling combined with TOF SIMS directly verifies that lattice oxygen of LiCoO2 (LCO) serves as the predominant oxygen source for LixPOyFz in CEI, clarifying the long debated LiPF6 decomposition mechanism at the cathode inte rface. 3 The OV mediated strategy endows LCO with 71.1% capacity retention after 600 cycles at 1 C (3–4.4 V) (vs. 23.9% for bare LCO) and achieves universal applicability in 4.5 V high voltage systems and NCM811 cathodes, establishing a new design principle for stable high performance cathodes.